Get an answer in 5 minutes
We'll notify as soon as your question has been answered.
Negative sign sorry
The negative sound is not inside the brackets so the y value changes by a factor of negative one. Hence the answer is (-3,-4)
Sorry, misread the question Y=-f(x) X =-3 Y=-f(-3) Y= -4 So answer is (-3,-4) Tldr, the graph has been flipped vertically so keep your X value consistent and make your y value negative
As we have y=-f(x) we have the negative value for f(x) Say you had f(x)=x², then y=-f(x) would be y=-x² So we keep the X value consistent F(4) = -3 So y= -f(4) = --3 = 3 So the value is (4,3)
Asked by Omar
-3, 11, 49, 123, ...
Asked by Lois
4y when y=-3
Asked by Alayna
10th term of n^2-3